P026 Feasibility and acceptability of a novel approach to sleep disorder screening and management for prospective shift workers. (9th November 2022) - Brown, B; Adams, R; Wanstall, S; Crowther, M; Rawson, G; Vakulin, A; Lechat, B; Rayner, T; Eastwood, P; Reynolds, A
Abstract: Introduction: Sleep disorders negatively impact health and occupational safety. Individuals commencing shift work with an undiagnosed sleep disorder may be at an increased risk of negative health and safety outcomes due to the addition of sleep schedule interruption associated with shift work. The aim of this study was to assess the feasibility and acceptability of screening for, and treating, sleep disorders in pre-service shift workers. Methods: Paramedic students were invited to participate in an intervention comprising of sleep disorder screening (obstructive sleep apnoea, insomnia, restless legs syndrome) and 15 weeks of non-invasive sleep monitoring (Withings Sleep Analyser) with regular follow-up (3, 6, and 12 weeks). Those at risk of a sleep disorder were contacted by the study physician and offered treatment pathways for their identified disorder (primary care or sleep specialist). Feasibility and acceptability will be assessed by a) reaching recruitment targets, b) participation rates, and c) qualitative interviews at 6 and 12 weeks. Results: Thirty participants are currently active in the trial with 63% female and an average age of 23 years. Seventeen participants (57%) met criteria for a sleep disorder based on baseline data and treatment pathways were initiated in July 2022 with a planned completion date of October 2022. Discussion: Participation rates, sleep parameters (collected through the sleep monitoring device), objective and subjective sleep disorder severity, and qualitative findings about feasibility and accessibility will be presented. Findings from this study will provide insight into barriers associated with accessing treatment for sleep disorders within pre-service shift workers.